2013
DOI: 10.1021/jp306976p
|View full text |Cite
|
Sign up to set email alerts
|

Application of the Multi-Step EPD Technique to Fabricate Thick TiO2 Layers: Effect of Organic Medium Viscosity on the Layer Microstructure

Abstract: In the present study, electrophoretic deposition (EPD) was used to obtain dense layers of TiO(2) in four organic media-methanol, ethanol, 1-propanol, and butanol-with different TiO(2) nanoparticle concenterations of 1-8 g/L. Microstructural study of the obtained layers by scanning electron (SEM) and optical microscope (OM) revealed that the multistep EPD technique could effectively prevent crack formation across the layer compared with the single-step method and will consequently increase the critical cracking… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 34 publications
1
10
0
Order By: Relevance
“…The stability of suspensions in terms of zeta potential was found to be around +40 mV for the three systems and therefore, the electrophoretic mobility of the particles was confirmed to depend on the ratio between the dielectric constant and the viscosity of the solvent. Under these conditions, and as observed also by Farrokhi-Rad et al [42] and Sadeghi et al [43,44], the lower the dielectric constant ( = 18.3 for isopropanol) and the higher the viscosity (Á = 1.945 mPa s for isopropanol), the lower would be the electrophoretic mobility and therefore, the deposition yield.…”
Section: Influence Of the Suspension And Epd Parameterssupporting
confidence: 79%
See 3 more Smart Citations
“…The stability of suspensions in terms of zeta potential was found to be around +40 mV for the three systems and therefore, the electrophoretic mobility of the particles was confirmed to depend on the ratio between the dielectric constant and the viscosity of the solvent. Under these conditions, and as observed also by Farrokhi-Rad et al [42] and Sadeghi et al [43,44], the lower the dielectric constant ( = 18.3 for isopropanol) and the higher the viscosity (Á = 1.945 mPa s for isopropanol), the lower would be the electrophoretic mobility and therefore, the deposition yield.…”
Section: Influence Of the Suspension And Epd Parameterssupporting
confidence: 79%
“…The employment of different alcoholic media has been studied by different authors [42][43][44], focusing on the influence of pK a values, vapor pressures, viscosities, or dielectric constants of the alcohols on both the suspension stability and the final quality of the coatings. In this sense, Farrokhi-Rad and Ghorbani, [42] studied the deposition of titania nanoparticles with an average size of 5 nm (Sigma-Aldrich Corporation, USA) using methanol, ethanol and butanol in the presence of triethanolamine (TEA) as a dispersant, and reported that the lower the pK a of the alcohol, the higher the absolute value of zeta potential, which implies higher stability of the particles.…”
Section: Influence Of the Suspension And Epd Parametersmentioning
confidence: 99%
See 2 more Smart Citations
“…For repeatable EPD results an additive usually should be used as a charging agent. Polyethyleneimine (PEI) is a cationic polyelectrolyte that has been widely used in EPD processes in aqueous and nonaqueous suspensions …”
Section: Introductionmentioning
confidence: 99%